Long Noncoding RNA EZR-AS1 Regulates the Proliferation, Migration, and Apoptosis of Human Venous Endothelial Cells via SMYD3 - You, Ganhua (Biomed Res Int, 2020)
Numerous studies have shown that long noncoding RNAs (lncRNAs) play essential roles in the development and progression of human cardiovascular diseases. However, whether lncRNA ezrin antisense RNA 1 (EZR-AS1) is associated with the progression of coronary heart disease (CHD) remains unclear. Accordingly, the aim of the present study was to evaluate the role of lncRNA EZR-AS1 in patients with CHD and in human venous endothelial cells (HUVECs). The findings revealed that lncRNA EZR-AS1 was highly expressed in the peripheral blood of patients with CHD. In vitro experiments showed that the overexpression of EZR-AS1 could enhance proliferation, migration, and apoptosis by upregulating the expression of EZR in HUVECs; downregulation of lncRNA EZR-AS1 resulted in the opposite effect. lncRNA EZR-AS1 was also found to regulate SET and MYND domain-containing protein 3 (SMYD3), a histone H3 lysine 4-specific methyltransferase, which subsequently mediated EZR transcription. Collectively, these results demonstrate that lncRNA EZR-AS1 plays an important role in HUVECs function via SMYD3 signaling.